Ameliorating effect of transcutaneous electroacupuncture on impaired gastric accommodation induced by cold meal in healthy subjects. Issue 3 (26th February 2016) - Huang, Zhihui; Zhang, Nina; Xu, Feng; Yin, Jieyun; Dai, Ning; Chen, Jiande DZ
Abstract: Background: Impaired gastric accommodation is recognized as one of major pathophysiologies in functional dyspepsia and gastroparesis. Electroacupuncture has been shown to improve gastric accommodation in laboratory settings. It is, however, unknown whether it exerts similar ameliorating effect in humans and whether needleless transcutaneous electroacupuncture (TEA) is also effective in improving gastric accommodation. Aim: The aim was to investigate the effects of TEA on gastric accommodation, gastric slow waves, and dyspeptic related symptoms. Methods: Thirteen healthy volunteers were studied in four randomized sessions: control, cold nutrient liquid, cold nutrient liquid + sham‐TEA, and cold nutrient liquid + TEA. The subjects were requested to drink Ensure until reaching maximum satiety. The electrogastrogram (EGG) and electrocardiogram (ECG) were recorded to assess the gastric and autonomic functions respectively. Results: 1) Gastric accommodation was reduced with the cold drink in comparison with the warm drink ( P = 0.023). TEA improved the impaired gastric accommodation from 539.2 ± 133.8 ml to 731.0 ± 185.7 ml ( P = 0.005). 2) The percentage of normal gastric slow waves in six subjects was significantly decreased in the cold session ( P = 0.002) and improved in the TEA session ( P = 0.009 vs sham; P < 0.001 vs cold). 3) TEA showed significant improvement in the bloating (80.8 ± 5.7 vs 61.2 ± 26.2, P = 0.011), postprandial fullness (48.1 ± 12.0 vs 34.2 ± 21.2, P = 0.042), and nausea (29.6 ± 10.9 vs 19.2 ± 11.2, P = 0.026) in comparison with sham‐TEA session. 4) Neither cold drink nor TEA altered vagal activities ( P > 0.05). Conclusions: TEA improves impaired gastric accommodation and slow waves induced by cold drink and the effect does not seem to be mediated via the vagal mechanisms.